The Effect of Talent Management and Work Motivation on Employee Performance: A Systematic Literature Review - Didin Sjarifudin; Erwin Barita Maniur Tambunan; Jakfat Haekal; Tubagus Hedi Saepudin (Greenation Research & Yayasan Global Resarch National, 2025)
Employee performance represents the achievements, work capabilities, and outcomes produced by individuals in an organization. It plays a crucial role in helping companies reach their strategic goals by leveraging high-quality human resources. Performance is measured by the quality and quantity of work accomplished in alignment with an employee's responsibilities. To enhance performance, organizations require skilled and talented employees who are driven to contribute effectively. Work motivation serves as a key factor in enabling employees to perform at their best. This study explores the relationship between talent management, work motivation, on employee performance through a systematic literature review. The article aims to develop a hypothesis on the influence of these variables, providing a foundation for future research. Data sources include online academic libraries, Google Scholar, Mendeley, and other open-access research platforms. The study adopts a library research method, utilizing e-books and peer-reviewed journal articles to examine existing findings. The results indicate that both talent management and work motivation significantly impact employee performance. Effective talent management strategies contribute to better performance outcomes, while work motivation serves as a crucial driver in enhancing employee productivity and engagement.